Evaluation of interproximal crestal bone loss around Straumann implants after the 1 st year of loading in panoramic radiography - Mehrdad Abdinian; Morteza Bonakdarchian; Reyhaneh Faghihian; Marzieh Yousefian (SRM Journal of Research in Dental Sciences, 2016)
Background: The marginal bone loss (MBL) around implants following restoration is used as a reference for evaluating implant success and survival. The aim of this study was to measure MBL around Straumann implants after 1 year of loading. Materials and Methods: The subjects of this prospective cross-sectional study were 81 patients (46 men, 35 women) receiving 289 Straumann implants. They were treated at a private office in Isfahan. The MBL was measured by two panoramic radiographs: the first one was taken immediately after loading and the second one was taken 1 year later. The data were analyzed by SPSS 11.5 (SPSS Inc., Chicago, Illinois, USA) software. Paired samples t-test and independent samples t-test were used to analyze the data. Results: The mean distal, mesial, and overall bone losses around implants were calculated 0.598, 0.688, and 0.643 mm, respectively (P > 0.157). Conclusion: This study has shown no significant differences of MBL regarding implant sides (mesial and distal) and location (maxilla and mandible).